PENGARUH NILAI TUKAR (IDR/USD), STRUKTUR MODAL, PROFITABILITAS TERHADAP RETURN SAHAM : STUDI EMPIRIS PADA PERUSAHAAN-PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE DI BEI - B31110045, STEFFEN (Jurnal Manajemen Update, 2017)
This study aims to determine the effect of the exchange rate (IDR / USD), capital structure and profitability on stock returns either simultaneously or partial. The population in this study is the property and real estate company listed on the Indonesia Stock Exchange during the period 2009-2013. Samples were examined as many as 15 companies. The independent variables studied were covering Exchange, capital structures (DER), and profitability (ROE). The data used is secondary data and analyzed using multiple linear regression (uiji F, t test, and the coefficient of determination) by means of the classical assumption mrliputi normality test, linearity, multicollinearity test, heteroscedasticity test and autocorrelation test. The results obtained F-count value 5.736 and significant value of 0.001. Due to the significant value of less than 5%, or 0.05, then the model research has met the eligibility specifications multiple regression model so that it can be done further analysis by the t test. Partially, the exchange rate (IDR / USD) significantly affects the return Shaam. While the exchange rate variable and capital structure (DER) showed a significant effect on stock returns. Variable profitability (ROE) not significant effect on stock returns. Based on these results it can be concluded that the company's management in order to maintain capital structure and the company should also be able to manage profitability effectively and efficiently in order to obtain a high return stock. Keywords: Exchange Rate (IDR / USD), Capital Structure (DER), profitability (ROE) and Return Shares.